Growth response and lipid content of chlorococcum humicola Dil.01 under varying regimes of sodiumnitrate concentration and photoperiod and detection of the ACCase-Encoding gene - Sikat, Gelito Joseph Mojado (Institute of Biology, College of Science, University of the Philippines Diliman, 2010)
Lipids from microalgae are considered to be the oils for future sustainable biodiesel production. However, relatively high production costs due to low lipid productivity have been one of the major obstacles impeding their commercial production. The present work studied the effects of nitrogen concentrations and photoperiods on cell growth and lipid accumulation, as well as the detection of the ACCase-encoding gene in chlorococcum humicola Dil. 01. Growthat low concentration of NaNO3 (0.0015 g/L) and subsequent increasing nitrate concentrations (0.015 and 3.000 g/L) did not significantly vary compared to the control set-u. The maximum growth rate occurred at the 20:4 light/dark regime. The growth was stable in concentrations of NaNO3 ranging from 0.0015 to 3.000 g/L, while the highes lipid content of about 20-23 % g/g of dry cell weight occurred in the lowest nitrate concentration of 0.0015 g/L. Varying photoeriods did not give significant differences agains the control albeit, the highest lipid content was recorded in longer light period of 20 hours (20:4) and relatively lower lipid was obtained in an equal length photoperiod (12:12). Fatty acid profiles revealed the presence of oleic acid which is known to be a main component of biodiesel, which consisted up to 27% of total fatty acids in C. humicola Dil. 01. In addition, cultures in low-nitrate concentration mediu also yielded high values of almitc acid, which constituted about 37.8 % (mol/mol) of the overall lipid content. The presence of an ACCase-encoding gene was also detected through PCR. This study embodies a targeted heteromeric subunit of the ACCase protein in which the nucleic acid encodes the gene, accD. Generated PCR products were sequenced and a phylogenetic tree was constructed. Phylogenetic analysis of the accD gene of C. humicola Dil. 01 formed a group with the microalgae chlorella vulgaris within the same clade as supported by high bootstrap value. Construction of the phylogenetic tree clarified the grouping of the ACCase-encoding gene present in C. humicola Dil.01 from higher plants and bacteria